An alternative conics drawing algorithm on a hexagonal grid using method of deviation. (10th April 2015) - Prabukumar, Manoharan; Ray, Bimal Kumar
In this paper, the algorithms to scan converting conics on hexagonal grid using method of deviation are proposed. The method of deviation computes the pixel nearest to the analogue curve using only integer arithmetic. The proposed algorithm is compared favourably with the latest conics drawing algorithm on hexagonal grid. The idea may be applied to scan converting any arbitrary curves. The transformation function to convert Cartesian coordinate system to hexagonal coordinate system is also proposed.